"Our poverty is a world full of dreams": reforming the World Bank (2005)
Under what circumstances do international organizations change their operations and routines? Examining the recent Strategic Compact reform initiative, we argue that change in the World Bank is 'triggered' by a complex set of factors stemming from changed interests and norms in the Bank's environment. The process of change, however, is something shaped by organizational culture, which is defined as the deeply embedded ideologies, norms, and routines that govern the expectations and behavior of bureaucratic staff. This organizational culture represents the internal friction that propels change in a slow, path-dependent direction that produces outcomes that are not necessarily congruent with the preferences of the organization's powerful shareholders or the intentions of internal reform initiators.